2012
DOI: 10.3141/2313-03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substructure Stiffness on Performance of Steel Integral Abutment Bridges under Thermal Loads

Abstract: This paper presents a study that investigated the effect of substructure stiffness on the performance of short- and medium-length steel integral abutment bridges (IABs) built on clay under thermal load effects. Various parameters, such as pile size and orientation, pile type, and foundation soil stiffness, were considered in the study. Detailed, three-dimensional (3-D), finite element (FE) models were developed to capture the behavior of IABs. Field measurements from a IAB were used to validate the 3-D FE mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Integral bridge building in Europe was summarized by White et al in 2010 [9] and more recently in Germany by Pak and Seidl [10]. Previous research on the subject has mainly addressed the thermal load effect [11][12][13], time-dependent deformations due to creep and shrinkage [14][15][16], and seismic loading [17][18][19]. Little published work has considered live load distribution in such bridges, except for the work of Dicleli, Yalcin and Erhan, which is summarized below.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Integral bridge building in Europe was summarized by White et al in 2010 [9] and more recently in Germany by Pak and Seidl [10]. Previous research on the subject has mainly addressed the thermal load effect [11][12][13], time-dependent deformations due to creep and shrinkage [14][15][16], and seismic loading [17][18][19]. Little published work has considered live load distribution in such bridges, except for the work of Dicleli, Yalcin and Erhan, which is summarized below.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the difference is more likely attributed to the difference in the in-situ soil conditions and or change in the soil properties such as the soil density with time as the bridge undergoes cycles of thermally induced displacements. Albhaisi et al (2012) investigated the effect of substructure stiffness on the performance of short and medium length steel integral abutment bridges built on clay under thermal loading effects. Detailed 3D finite element models were developed using LUSAS software and a parametric study was carried out.…”
Section: Thermal Effectmentioning
confidence: 99%
“…Also, the foundation soil can affect performance of the bridge especially during negative thermal loading (Civjan et al, 2007). While Albhaisi et al (2012) concluded that clay stiffness and the foundation soil have a minor effect on the displacement of the top of the abutment. Upon this contradiction about the role of foundation soil on the bridge performance, two foundation soil, namely: stiff clay and medium dense sand, were adopted to emphasize the role of foundation soil on the performance of horizontally curved IAB.…”
Section: Soil Conditionsmentioning
confidence: 99%
“…This nonlinear behavior is simplified by using an elastoplastic curve displayed in Figure 4 with the dashed line. The elastic portion is defined with a slope equal to the secant soil modulus (E s ) and the soil modulus for clay can be calculated with the following expression: For a foundation supported by clay, the soil was approximated with elastic spring elements having a spring constant equal to E s (12).…”
Section: Soil-pile Interactionmentioning
confidence: 99%
“…These guidelines provide useful design examples based on experience in the design of IABs but do not provide theoretical approach for the analysis. The authors conducted a detailed parametric study to investigate the effect of substructure stiffness on the performance of steel IABs using 3-D FE models (12,13). On the basis of the results of this parametric study, a simple approach was derived to calculate the displacement and the rotation induced by thermal loading in IABs.…”
mentioning
confidence: 99%